Conformidade de memória: as influências de informações provindas de fontes externas confiáveis e não-confiáveis durante o reconhecimento - Matheus Philippe de Faria Santos (2021)
Considering the phenomenon of memory conformity (e.g., how our memories can be influenced by third-party reports), the relevance of eyewitness accounts for legal and criminal investigations, the impact that misinformation phenomena have caused, and the theoretical debate about the processes involved in memory evocation, the present study sought to investigate how information from third parties affects recognition accuracy and confidence. To this purpose, a word recognition memory experiment was conducted with 80 participants who received cues from a third-party concerning the status of the item to be recognized. Participants were explicitly informed that the cues came from a previous participant in the same experiment who had gotten 75% (reliable source) or 25% (unreliable source) of the responses right. It was possible to observe that the phenomenon of memory conformity tends to occur for sources that we consider reliable and/or potentially informative without, however, being linked to improved performance. No memory conformity or accuracy changes could be found to occur for the unreliable source. High confident responses showed high recognition and recognition rejection accuracy rates. Furthermore, meta-cognitive judgment regarding the frequency of use and impact of the cues on one's own memory judgment was found to be significantly inaccurate. We have found that the relationship between accuracy and confidence tends to be strong, and the dual-process theory more supported. We point out that we tend to conform only to potentially informative (e.g., credible) sources, even though such behavior is not adaptive.